TANGGUNG JAWAB PELAKU USAHA JAJAN PASAR TERHADAP KONSUMEN YANG MENGALAMI KERACUNAN MAKANAN - Teuku Sulthan Masy'al (2022)
Many business actors produce products with various qualities and various qualities. Especially in terms of food, people no longer prioritize their daily food but prefer to buy from restaurants although it is not certain whether the ingredients used to serve food in the restaurant are clean and safe for consumption. Food served by restaurants can cause food poisoning if the food processing materials used are not guaranteed to be clean. Food poisoning can occur when buying food at restaurants. Protection of consumers is considered increasingly important in terms of material and form, given the rapid development of science and technology that encourages productivity and efficiency of business actors for the goods and/or services they produce. With the Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection, it is hoped that consumer protection efforts in Indonesia can be further improved so that the position of consumers is not always in a weak position and business actors can also further improve the quality of goods and/or services offered to consumers.. The approach method in this research is normative juridical. Data was collected by means of library research and interviews. The data collected includes primary and secondary data. The research data will be analyzed qualitatively to describe the problem systematically, factually, and accurately. The result of this research is that until now the Consumer Protection Act has not been implemented properly. Business actors as producers of goods and/or services pay less attention to their obligations, as well as the rights of consumers. To provide an understanding to the general public and business actors regarding the Consumer Protection Act, it can be implemented by conducting consumer guidance such as outreach activities or seminars.